Analisis Evaluasi Kebijakan Pengembangan Pariwisata Super Prioritas Berkelanjutan di Labuan Bajo Nusa Tenggara Timur - Jelianti Yunita Salukh; David B.W. Pandie; Apriana H.J. Fanggidae (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
This study aims to describe the evaluation of central and local government policies through 5 key tourism factors namely Amenities, Attractions, Accessibility, Awarness (Tourism concern) and Accommodation, based on CBT for sustainable super priority tourism development. This study uses a qualitative descriptive method, using primary and secondary data and interviews with 11 informants related to the Analytical Hierarchy Process analysis tool. The research results show that the development of priority levels of tourism policies that need to be carried out by the government consists of accessibility, availability of transportation as access, supported by natural attractions, amenities where banking facilities are available, namely Bank, Money Chancer, ATM, then Awareness to create MSME empowerment, and finally Accommodation Availability of decent, safe, comfortable and clean places to stay. These five things are the top priority in the formation of the Labuhan Bajo Super Priority tourism policy.